Contemporary Theatre Directors About the Art of Directing and Theatre Pedagogy - POP-CURȘEU, Ștefana (Studia Universitatis Babeș-Bolyai Dramatica, 2022)
In order to have a view as broad as possible on contemporary theater making, including theatre and directing pedagogy, I thought of a few questions to be answered by theater professionals, answers that would give a consistent image of the state of facts and of future openings for theatre/stage directing. I wondered if the complex definition given by Stanislavsky more than a century ago, at the very beginning of the director’s era, or at least, parts of it, are still valid.